﻿GC-MS analysis of bioactive compounds and antibacterial activity of nangka leaves (Artocarpus heterophyllus Lam) - Indah Yani Br. Tambunan; Esther Siringo-Ringo; Mastiur Julianti Butar-Butar; Kasta Gurning (Pensoft Publishers, 2023)
Nangka is a plant that has various kinds of potential both because of the nutritional content provided through the fruit and also part of the content of bioactive compounds contained in the leaves. This study aims to identify the content of bioactive compounds and determine their content using GC-MS and determine the potential antibacterial activity against E. coli, S. aureus, S. epidermidis, S. typhi, P. acnes from the ethanol extract of nangka leaves (Artocarpus heterophyllus Lam). Screening results showed positive containing phenolic groups, flavonoids, tannins, saponins, and alkaloids. The results of determining the content of bioactive compounds for phenolics, tannins and flavonoids were 27.654±0.054 mg GAE/g d.w ethanolic extract, 0.46±0.017 mg TAE/g d.w ethanolic extract and 2.978±0.192 mg QE/g d.w ethanolic extract. GC-MS analysis showed the content of octadecanoic acid with a retention time of 36.489 minutes with a concentration of 29.91% and the ethanolic extract of nangka leaves had good potential activity as an antibacterial.